The relationship of safe and participatory school environments and supportive attitudes toward violence: Evidence from the Colombian Saber test of Citizenship Competencies. (March 2015) - Diazgranados, Silvia; Noonan, James
In Colombia, reducing levels of interpersonal and community violence is a key component of the country's approach to citizenship education. In this study, we use data collected during the 2005 Saber test of Citizenship Competencies to examine the relationship of school environments and individual students' supportive attitudes toward violence among 97, 971 students in 1649 schools. Using multi-level Tobit analysis with school random intercepts and regional fixed effects, we find that children taught in safe and participatory climates endorse attitudes less supportive of violence, with the effect of participatory climates almost double that of safe climates. Constructing a typology of four classroom environments, by crossing the two dimensions of safety and participation, we conclude that school environments that are safe and participatory lead to the least supportive attitudes toward violence, more than 1 standard deviation lower than unsafe and non-participatory school environments. Implications, limitations, and areas for future research are discussed.